2022
DOI: 10.3389/fphy.2022.963795
|View full text |Cite
|
Sign up to set email alerts
|

A novel image encryption scheme based on memristive chaotic system and combining bidirectional bit-level cyclic shift and dynamic DNA-level diffusion

Abstract: In recent years, many researchers have leveraged various memristors to design many novel memristive chaotic systems with complex dynamics. Compared with other chaotic systems, applying these memristive chaotic systems to image encryption is expected to solve some key problems in this field. Therefore, exploiting a recently reported memristive chaotic system, this paper proposes a novel image encryption scheme based on the memristive chaotic system and combining bidirectional bit-level cyclic shift and dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…By utilizing a memristive chaotic system and combining it with bidirectional bit-level cyclic shift and dynamic DNA-level diffusion, the proposed scheme offers enhanced security and resistance to attacks. This can help protect sensitive image data in IoT applications, ensuring the privacy and integrity of the transmitted or stored images [53].…”
Section: Related Workmentioning
confidence: 99%
“…By utilizing a memristive chaotic system and combining it with bidirectional bit-level cyclic shift and dynamic DNA-level diffusion, the proposed scheme offers enhanced security and resistance to attacks. This can help protect sensitive image data in IoT applications, ensuring the privacy and integrity of the transmitted or stored images [53].…”
Section: Related Workmentioning
confidence: 99%
“…In [ 17 ], Li et al suggested an image encryption scheme based on DNA operations, which exploits non-adjacent blocks and permutation blocks to scramble the input image and then employs dynamic bidirectional diffusion to obtain the final ciphertext image. Similarly, considering the substitution effect of dynamic DNA encoding, two image encryption schemes using scrambling and diffusion architectures were proposed successively [ 18 , 19 ]. In [ 20 ], Feng et al also developed an image encryption scheme based on image filtering and discrete logarithm, in which image filtering can diffuse a large number of pixels at the same time, and discrete logarithm transformation exerts the encryption effect of pixel substitution.…”
Section: Introductionmentioning
confidence: 99%
“…Some encryption schemes combined various mathematical theories of interesting problems [ 13 , 14 ]; for example, Josephus Problem was employed in [ 13 ] for designing a secure and efficient image encryption scheme. Some encryption schemes combine DNA coding technologies to acquire the confusion effect similarly to S-box [ 15 , 16 , 17 ]. Most schemes encrypt the image as a whole, but a few methods divide the image into several small blocks for encryption; e.g., Zhang et al.…”
Section: Introductionmentioning
confidence: 99%